Sistem Informasi Peralatan Gardu Induk berbasis Web - Bagus Dwi Saputro; Edy Widodo; Muhamad Fatchan (DPPM Universitas Pelita Bangsa, 2022)
This research is motivated by the lack of supporting facilities to facilitate work in PLN institutions. PT. PLN (Persero) is a state-owned company engaged in electricity. In the structure of PLN there is a section called the Substation. Based on the survey results, there is one obstacle experienced by the PLN Substation, namely the process of storing tool data and documents that have not been structured and are still stored manually. This deficiency has an impact on the process of searching for data or documents, so that the search is not efficient and effective. Therefore, this research was made aiming to help facilitate the work of PLN Substation employees in terms of storing equipment and document data. The purpose of this research is to develop and improve the existing system so that it becomes a program that is efficient, fast, precise, easy to operate and has high mobility. The program to be built is entitled